Mobile ad-hoc and sensor networks : 13th International Conference, MSN 2017, Beijing, China, December 17-20, 2017, Revised selected papers /: 13th International Conference, MSN 2017, Beijing, China, December 17-20, 2017, Revised selected papers. (2018) - Unknown
No abstract available